Magnetic proximity effect in Pr₀.₅Ca₀.₅MnO₃/La₀.₇Sr₀.₃MnO₃ bilayered films - Prokhorov, V.G.; Kaminsky, G.G.; Flis, V.S.; Kim, J.M.; Eom, T.W.; Park, J.S.; Lee, Y.P.; Svetchnikov, V.L. (Физика низких температур, 2012)
The magnetotransport properties of Pr₀.₅Ca₀.₅MnO₃/La₀.₇Sr₀.₃MnO₃ bilayer, and Pr₀.₅Ca₀.₅MnO₃ and La₀.₇Sr₀.₃MnO₃ films, deposited on LaAlO₃ (001) substrate by pulse laser deposition have been investigated. The x-ray diffraction and high-resolution electron-microscopy analysis reveals that lattice parameters for the constituent sublayers in the bilayer are very close to that for the individual films. It was found that a ferromagnetic transition in the La₀.₇Sr₀.₃MnO₃ sublayer significantly modifies the magnetotransport properties of the Pr₀.₅Ca₀.₅MnO₃ constituent sublayer, owing to occurrence of a magnetic proximity effect. The main evidences for this effect are an appearance of the exchange bias interaction between the constituent sublayers; a localizedto-itinerant crossover in the system of polarized electrons, which results in formation of the Griffiths-like ferromagnetic state; and an unusual polaron transport of carriers. The experimental results have been analyzed within the framework of modern theoretical approaches.